Preservation of coagulation efficiency of Moringa oleifera, a natural coagulant. - Saed, Katayon; Ng, S.C.; Megat Mohd Noor, Megat Johari; Abdullah, Abdul Ghani Liew (Korean Society for Biotechnology and Bioengineering, 2006)
In recent years, there has been an interest to useMoringa oleifera as the natural coagulant due to cost, associated health and environmental concerns of synthetic organic polymers and inorganic chemicals. However, it is known thatM. oleifera as the natural coagulant is highly biodegradable and has a very short shelf life. This research was carried out to investigate the effects of storage temperature, packaging methods, and freeze-drying on the preservation ofM. oleifera seeds powders. Non freeze-driedM. oleifera was prepared into different packaging namely open container, closed container and vacuum packing, whilst, freeze-driedM. oleifera was stored in closed container and vacuum packing. Each of the packaging was stored at room temperature (30 to 32°C) and refrigerator (4°C). The turbidity removal efficiencies of storedM. oleifera were examined using jar test at monthly interval for 12 months. The results indicated that non freeze-driedM. oleifera kept in the refrigerator (4°C) would preserve its coagulation efficiency. In addition, closed container and vacuum packing were found to be more appropriate for the preservation of non freeze-driedM. oleifera, compared to open container. Freeze-driedM. oleifera retained its high coagulation efficiency regardless the storage temperature and packaging method for up to 11 months. Besides, higher increment in zeta potential values for water coagulated with freeze-driedM. oleifera indicated the higher frequency of charge neutralization and better coagulation efficiency of freeze-driedM. oleifera, compared to non freeze-dried seeds. As a coagulant,M. oleifera did not affect the pH of the water after treatment.